# What are the formulas for algebra 1?

## What are the formulas for algebra 1?

x2 – x1. Linear Equations. Slope-intercept Form: y = mx + b. Point-slope Form: y – y1 = m(x – x1) Standard Form: Ax + By = C.

• • r n – 1.
• Compound Interest Formula. A = P(1 + r } n )
• nt.
• Quadratic Formulas. Quadratic Equations. Standard Form: y = ax2 + bx + c. Vertex Form: y = a(x – h)2 + k.
• −b ± √
• _______
• b2 – 4ac.
• ### Is algebra 1 an intermediate algebra?

College algebra is a transfer level algebra course offered at many California community colleges and CSU campuses and generally has a prerequisite of intermediate algebra….The California Community College and Intermediate Algebra.

1 2 3
Algebra I Elementary Algebra Beginning Algebra Algebra II Intermediate Algebra College Algebra Statistics Mathematical Ideas

#### What are the 14 identities?

These identities can be given as under:

• Identity-I: a2 – b2 = (a + b) (a – b)
• Identity-II: a3 – b3 = (a – b) (a2 + ab + b2)
• Identity-III: a3 + b3 = (a + b) (a2 – ab + b2)
• Identity-IV: a4 – b4 = (a2 – b2) (a2 + b2)

What kind of math is intermediate algebra?

Intermediate Algebra is a branch of mathematics that substitutes letters for numbers and uses simplification techniques to solve equations. Algebraic equations: A scale, what is done on one side of the scale with a number is also done to the other side of the scale.

How can I learn algebra 1 fast?

6 Hidden Tricks for Getting Ready to Learn Algebra Fast

1. Make Up Tricks to Remember the Rules. The one good thing about algebra – and math in general – is that the rules don’t change.
2. Learn Shortcuts.
3. Get to Know the Calculator.
4. Join a Study Group.
5. Hire a Tutor.
6. Encourage Your Child to Ask Their Teacher for Help.

## What are the 8 algebraic identities?

The standard algebraic identities are:

• (a + b)2 = a2 + 2ab + b.
• (a – b)2 = a2 – 2ab + b.
• a2 – b2 = (a + b)(a – b)
• (x + a)(x + b) = x2 + (a + b) x + ab.
• (a + b + c)2 = a2 + b2 + c2 + 2ab + 2bc + 2ca.
• (a + b)3 = a3 + b3 + 3ab (a + b)
• (a – b)3 = a3 – b3 – 3ab (a – b)